An exceptionally well-preserved fossil Kalligrammatid from the Jehol Biota - Yang, Qiang; Zhao, YunYun; Ren, Dong (Chinese science bulletin, 2009)
A new species of Neuroptera, Sophogramma lii sp. nov. is described and illustrated in this paper. This new species is assigned to Sophogramma Ren of Kalligrammatidae, mainly based on its humeral recurrent veins, the basal cell present between posterior branch of media at base of wing, etc. The new species is distinguished from all other Sophogramma species on the difference of wing venation. This exceptionally well-preserved specimen is recovered from the Yixian Formation, Huangbanjigou, located near Beipiao City, in western Liaoning Province. The genus diagnosis has been emended based on new characters shown in this new species. Based on a summary of localities, distribution and geological ages of all genera and species of the Kalligrammatidae, we suggest that Kalligrammatids might have originated in Eastern Asia, especially in China. Function of the wing pigmentation is discussed briefly.